Effect Of Chloropyrifos And Malathion On Antioxidant Enzymes In Tomato And Brinjal - MAHNAZ NASRABADI; NIVEDITA GHAYAL; K. N. DHUMAL (International Journal of Pharma and Bio Sciences, 2011)
Modern agriculture associated with monoculturing has favoured noxious insects and pests. This has promoted a heavy reliance on synthetic pesticides to control and limit their spread. Amongst vegetables tomato and brinjal are very commonly used throughout India and especially in the state of Maharashtra. Because of this they have occupied maximum cultivable land as compared to other vegetables. However both the vegetables are highly susceptible to insect attack. To enhance the yield and net economic return from these vegetables, growers apply heavy doses of chloropyrifos and malathion, which generate xenobiotic / pollution stress on these crops leading to creation of reactive oxygen species (ROS) in them which culminate the plants into death through cellular damages. Scavenging of ROS through stimulation of antioxidant enzymes such as SOD, POD and PPO is the most adaptive mechanism for the tolerance of pollution. The results of the present investigation revealed that both the pesticides have caused highly significant stimulation in the activities of SOD, POD and PPO, and it increased with the increasing dose of chloropyrifos and malathion.